Automated testing in Microsoft Dynamics 365 Business Central : efficiently automate test cases for faster development cycles with less time needed for manual testing /: efficiently automate test cases for faster development cycles with less time needed for manual testing. (2021) - Vugt, Luc van
No abstract available